040 Central Mechanisms Contribute to Pro-Ejaculatory Response Induced by the Combination of Dopamine and 5-HT2 Receptor Agonist in Rats. (1st May 2022) - Yoshizumi, M.; Yonezawa, A.; Kimura, Y.; Watanabe, C.; Kawatani, M.; Sakurada, S.; Mizoguchi, H.
ABSTRACT: Introduction: Although we previously demonstrated in rats that combination of a dopamine (DA) receptor agonist and 5-HT2 receptor agonist potently and selectively facilitates the ejaculatory response through the activation of D2 -like and 5-HT2C receptors, these central mechanisms are not fully understood. We therefore investigated to clarify the target level of the pro-ejaculatory effects by combination of these agonists. Methods: The ejaculatory response was evaluated 30 min after drug administration by the presence of seminal materials on the paper towel as well as that adhering to the shaft of the penis. In addition, we examined isolated rat seminal vesicle contraction. Results: Intrathecal administration of 5-HT2 receptor agonist m-CPP (10 μg) but not in intracerebroventricular evoked the synergistic action for ejaculation in the combination with systemic administrated DA receptor agonist apomorphine (0.1 mg/kg, s.c.). Synergy effects of combination were completely inhibited by intrathecal 5-HT2C receptor antagonist SB242084 (10 μg). Intrathecal or intracerebroventricular apomorphine (1-10 μg) evoked the pro-ejaculatory effects in the combination with systemic administrated m-CPP (0.3 mg/kg, i.p.) The selective peripherally acting D2 -like receptor agonist carmoxirole did not evoked in the combination with m-CPP. Furthermore, the combination of apomorphine and m-CPP did not produce contraction of rat seminal vesicle. Conclusion: These results suggest that this synergistic action for ejaculation induces in the spinal or supraspinal level but not the peripheral sites. Furthermore, the present study suggests that the activation of the spinal ejaculatory pattern generator through 5-HT2C receptors is synergistically potentiated by both spinal and supraspinal DA receptors. Disclosure: Work supported by industry: no.